2006
DOI: 10.1158/1078-0432.ccr-06-0979
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanticity of Plasmid DNA Encoding Cytokines Fused to Immunoglobulin Fc Domains

Abstract: Purpose: Plasmid DNAs encoding cytokines enhance immune responses to vaccination in models of infectious diseases and cancer. We compared DNA adjuvants for their ability to enhance immunity against a poorly immunogenic self-antigen expressed by cancer. Experimental Design: DNAs encoding cytokines that affect T cells [interleukin (IL)-2, IL-12, IL-15, IL-18, IL-21, and the chemokine CCL21] and antigen-presenting cells [granulocyte macrophage colony-stimulating factor (GM-CSF)] were compared in mouse models as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The human CD8 transmembrane domain was fused to the mouse CD3 chain and to either the CD19-specific scFv from 19z1 to generate 19mz, or to the prostate-specific membrane antigen (PSMA) scFv from the Pz1 CAR, 5 to generate the control Pmz CAR. The fusion gene encoding the complete murine IL-12 with a serine-glycine repeat between the p35 and p40 chain-coding domains (mIL12f) was generously provided by Alan Houghton and Jedd Wolchok, 14 and modified to include an hCD8 leader peptide and an internal ribosome entry site (IRES).…”
Section: Generation Of Retroviral Constructsmentioning
confidence: 99%
“…The human CD8 transmembrane domain was fused to the mouse CD3 chain and to either the CD19-specific scFv from 19z1 to generate 19mz, or to the prostate-specific membrane antigen (PSMA) scFv from the Pz1 CAR, 5 to generate the control Pmz CAR. The fusion gene encoding the complete murine IL-12 with a serine-glycine repeat between the p35 and p40 chain-coding domains (mIL12f) was generously provided by Alan Houghton and Jedd Wolchok, 14 and modified to include an hCD8 leader peptide and an internal ribosome entry site (IRES).…”
Section: Generation Of Retroviral Constructsmentioning
confidence: 99%
“…[5][6][7] Furthermore, a number of cytokines (interleukin (IL)-2, -12, -15, -18, -21, and -24) have been tested as adjuvants in combination with DNA vaccines, with varying degrees of enhanced antitumor immunity. 8,9 We earlier reported that granulocyte macrophage colony-stimulating factor (GM-CSF) DNA enhanced antitumor immunity induced by hgp100 DNA vaccination in a mouse melanoma model. 10 However, in general, such adjuvant cytokines have not been shown to confer significant and consistent enhancement of antigen-specific cell-mediated immunity with DNA vaccine approaches, and the ability of tumors to escape the immune system has been a major obstacle to the development of effective tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we fuse the antigen mVEGFR2 with GPI signal peptide and Fc fragment, so that the antigen could be anchored on the cell membrane and be recognized by APCs more efficiently [17,18].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%